Empirical fragility curves for single-story precast industrial buildings extracted from the 2023 Turkiye earthquake survey data - Sisman, Rafet; Altunisik, Ahmet Can; Gunaydin, Murat; Okur, Fatih Yesevi; Yilmaz, Zafer; Sunca, Fezayil; Aslan, Banu; Sezdirmez, Tugrul; Taciroglu, Ertugrul (ELSEVIER SCI LTD, 2025)
An earthquake sequence comprising three major events with moment magnitudes of Mw7.7 (mainshock), Mw6.6 (aftershock), and Mw7.6 (mainshock) hit the southeastern regions of Turkiye on February 6, 2023. Eleven provinces were directly affected by these events, and thousands of buildings either collapsed or were heavily damaged. Post-event reconnaissance efforts began immediately, and a large team of engineers was commissioned and deployed to the region to document the damage on a building-by-building basis. These efforts yielded an extensive dataset that provides various features of the inspected structures and their assigned damage levels. The dataset contains industrial buildings, mainly single-story precast structures typical in the affected region and across Turkiye. The area struck by the earthquakes is an important industrialized region for the country, and thus, damage to the industrial buildings led to significant economic losses. This study aims to derive empirical fragility curves for typical industrial buildings of Turkiye so that seismic risks to that particular inventory by similar future events can be assessed at regional scales. The empirical fragility curves are obtained her ein for single-story precast industrial buildings only, classified into pre-and post-2000 constructions, with 1998 being the watershed year in related construction technologies and seismic design regulations. Two separate fragility sets are considered-one with three damage states and the other with a more refined four damage states. The curves are obtained with data from more than 4,000 structures and using multiple fitting schemes.
Keywords: Empirical fragility curves; Precast industrial buildings; Earthquake damage; Kahramanmaras earthquake sequence; DAMAGE DATA; RC BUILDINGS; Engineering